Proceedings of the first middle east congress on osteoporosis - Stevenson, John C (Royal Society of Medicine Services, 1987)
A collection of papers presented at a congress that focused on osteoporosis. Intended for professional public.
International congress and symposium series ; Number 118
Keywords: osteoporóza; Osteoporosis; osteologie